The spiral wave trajectory motion of particles is the only reason for the establishment of the Poincare regression theorem (Background radiation is not evidence of the big bang of the cosmic singularity) - Xie Ling (Annals of Mathematics and Physics - Peertechz Publications, 2022)
In short, an isolated and limited system will return to a state very close to the initial state in the long-term evolution process. For example, in a container, gas particles rotate in chaos and return to their initial position after a period of time. I have proved that everything is a spiral wave track (path) and has the property of wave: v = Fλ ; λ= uT. It is proved that any finite object (particle) has a common period: the nearest distance and the farthest distance. Such as the earth and the moon; Earth and the sun; The three bodies of the earth, the moon and the sun, and the comet and the earth all meet periodically. Particles also have this property. The principle is due to the periodicity of the spiral of an object. The Poincare regression theorem is proved by the spiral periodic wave pattern of the object. Mathematical classification code: 70F20;70F45;03D55;76Y99; 81V25; 37A55